2005
DOI: 10.1007/s10620-005-3067-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Insulin Enhances Intestinal Regrowth Following Massive Small Bowel Resection in Rat

Abstract: Experimental studies have suggested that insulin (INS) plays an important role in small intestinal growth and development. In the present study we investigated the effect of oral INS on structural intestinal adaptation and enterocyte proliferation and loss via apoptosis in a rat model of short bowel syndrome (SBS). Male Sprague-Dawley rats were divided into three experimental groups: sham rats underwent bowel transection, SBS rats underwent 75% small bowel resection, and SBS-INS rats underwent bowel resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Several in vitro and in vivo experiments have demonstrated that insulin and insulin-like growth factors enhance proliferation and diminish apoptosis in epithelial cells. We have previously observed similar effects of oral insulin on intestinal epithelial cell turnover in young rats after weaning [15], in rats after bowel resection [16] or adult rats after intestinal damage [17,18]. In contrast to these experiments, the current data suggest that OI supplementation in normal non-stressed adult rats exerts a mild inhibitory effect on microscopic intestinal mucosal parameters.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Several in vitro and in vivo experiments have demonstrated that insulin and insulin-like growth factors enhance proliferation and diminish apoptosis in epithelial cells. We have previously observed similar effects of oral insulin on intestinal epithelial cell turnover in young rats after weaning [15], in rats after bowel resection [16] or adult rats after intestinal damage [17,18]. In contrast to these experiments, the current data suggest that OI supplementation in normal non-stressed adult rats exerts a mild inhibitory effect on microscopic intestinal mucosal parameters.…”
Section: Discussionsupporting
confidence: 45%
“…The insulin concentration of 1u/ml in drinking water had an optimal effect in this study. We have also demonstrated the positive trophic effects of OI on the small intestinal mucosa in certain gastrointestinal disorders, including short bowel syndrome [16], intestinal ischemia-reperfusion [17], and methotrexate-induced intestinal mucositis [18].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The improvement in nutrient and energy digestibility has been attributed to the saponin content in fenugreek seed that stimulate insulin activity, which in turn positively impacts intestinal morphology and therefore nutrient absorption (Sukhotnik et al 2005;Khalaji et al 2011). In the present study, the improvements in N and GE digestibility did not translate into improvements in any of the sow response criteria measured.…”
Section: Discussionmentioning
confidence: 99%
“…Since insulin has trophic gut effects, we hypothesized that insulin may have a beneficial effect on gut growth and recovery in different gastrointestinal disorders. We have recently demonstrated that oral insulin exerts a strong stimulating effect on bowel re-growth following massive small bowel resection in a rat [18]. In a different experiment, we have shown that oral insulin does not prevent ischemic damage but accelerates intestinal recovery, enhances enterocyte proliferation, and decreases cell death via apoptosis following intestinal ischemia-reperfusion in jury in rats [19].…”
Section: Discussionmentioning
confidence: 94%